Practice-oriented solutions integrating intraoperative electron irradiation and personalized proton therapy for recurrent or unresectable cancers: Proof of concept and potential for dual FLASH effect - Calvo, Felipe A.; Ayestaran, Adriana; Serrano, Javier; Cambeiro, Mauricio; Palma, Jacobo; Meiriño, Rosa; Morcillo, Miguel A.; Lapuente, Fernando; Chiva, Luis; Aguilar, Borja; Azcona, Diego; Pedrero, Diego; et al. (Frontiers in Oncology, 2022)
Background Oligo-recurrent disease has a consolidated evidence of long-term surviving patients due to the use of intense local cancer therapy. The latter combines real-time surgical exploration/resection with high-energy electron beam single dose of irradiation. This results in a very precise radiation dose deposit, which is an essential element of contemporary multidisciplinary individualized oncology. Methods Patient candidates to proton therapy were evaluated in Multidisciplinary Tumor Board to consider improved treatment options based on the institutional resources and expertise. Proton therapy was delivered by a synchrotron-based pencil beam scanning technology with energy levels from 70.2 to 228.7 MeV, whereas intraoperative electrons were generated in a miniaturized linear accelerator with dose rates ranging from 22 to 36 Gy/min (at Dmax) and energies from 6 to 12 MeV. Results In a period of 24 months, 327 patients were treated with proton therapy: 218 were adults, 97 had recurrent cancer, and 54 required re-irradiation. The specific radiation modalities selected in five cases included an integral strategy to optimize the local disease management by the combination of surgery, intraoperative electron boost, and external pencil beam proton therapy as components of the radiotherapy management. Recurrent cancer was present in four cases (cervix, sarcoma, melanoma, and rectum), and one patient had a primary unresectable locally advanced pancreatic adenocarcinoma. In re-irradiated patients (cervix and rectum), a tentative radical total dose was achieved by integrating beams of electrons (ranging from 10- to 20-Gy single dose) and protons (30 to 54-Gy Relative Biological Effectiveness (RBE), in 10–25 fractions). Conclusions Individual case solution strategies combining intraoperative electron radiation therapy and proton therapy for patients with oligo-recurrent or unresectable localized cancer are feasible. The potential of this combination can be clinically explored with electron and proton FLASH beams.